Dieting 2.0!: Moderating effects of Instagrammers' body image and Instafame on other Instagrammers' dieting intention. (October 2018) - Jin, Seunga Venus; Ryu, Ehri; Muqaddam, Aziz
Abstract: Drawing from the literature on narcissism, social comparison, and eating disorder, two experiments examined the interaction effects of exposure to different types of body image presented in Instagrammers' photos, photo posters' Instafame, and peer Instagrammers' individual difference factors on dieting intention. Experiment 1 ( N  = 230) tested two-way interaction effects between Instagrammers' posts (selfies vs. group selfies vs. photos taken by others vs. neutral photos) and peer Instagrammers' individual difference factors (narcissism, social comparison, and eating disorder). Experiment 2 ( N  = 322) tested three-way interaction effects among Instagram posts (selfies vs. group selfies vs. photos taken by others vs. neutral photos), Instafame (high followers vs. low followers), and peer viewers' individual difference factors (narcissism, social comparison, and eating disorder). Experiment 1 provides robust findings about the moderating effects Instagrammers' photos have on the association between peer Instagrammers' individual difference factors and their dieting intention. Experiment 2 sheds some lights on the moderating roles of Instagrammers' photos and Instafame. The results of both experiments signify the importance of examining the influence of social media users' psychological characteristics in understanding the effects of exposure to social media posts. Theoretical contributions to the extant literature on body image and practical implications for social media-based health campaigns about weight management, dieting, and eating disorder are discussed. Highlights: Experiment 1 tested effects of Instagram photos and viewers' individual difference factors. Experiment 2 tested effects of photos, fame, and viewers' individual differences factors. Photo types moderate effects of narcissism and social comparison on dieting intention. Instafame levels moderate effects of narcissism and social comparison on dieting intention. Implications for Instagram-based campaigns about weight management are discussed.